Circulating tumor cells in oncology - D. I. Vodolazhsky; T. L. Nekhaeva; I. A. Baldueva (Сибирский онкологический журнал)
Purpose of the study: to identify general patterns in the presence of detectable amounts of circulating tumor cells (CTCs) negatively correlated with the overall survival of patients and their ability to form metastases in distant tissues and organs, as well as to summarize the biological properties and interactions of CTCs with other cell types during intravasation, circulation, extravasation, and colonization, which involve changes in CTC phenotypes that are regulated by many signaling molecules, including cytokines and chemokines. Material and Methods. We analyzed publications available from PubMed (https://pubmed.ncbi.nlm.nih.gov), Scopus (https://www.scopus.com/), Web of Science (https://apps.webofknowledge. com/WOS_GeneralSearch), Cancer Tomorrow (https://gco.iarc.fr/tomorrow/en), and Global cancer observatory (https://gco.iarc.fr) databases between 2000–2021 using the keywords “circulating tumor cells”, “biomarker”, “metastasis” and others. Results. Monitoring of blood levels of CTCs can have exceptional prognostic and monitoring implications. Liquid biopsy to detect CTCs and their progeny can be used to diagnose cancer in the general population, as well as to predict biomarkers in cancer patients. The improvement in the CTC detection technology and clinical trials in large prospective studies will increase the clinical usefulness of these marker cells. Understanding of their biology and interactions with other cell types, especially with the immune cells, and the development of CTC immunotherapy also holds great promise in cancer therapy. Conclusion. Currently, CTCs are not routinely used in clinical practice, but research in this area continues to accumulate the data on the clinical validity of CTC detection. This is due to the feasibility of monitoring the patient’s condition using liquid biopsy for the CTC detection. We present an overview of the clinical value of CTCs as a biomarker, as well as key studies examining the clinical usefulness of CTCs.